Reported preexposure prophylaxis use among male sex partners of HIV-positive men: 2016–2018. (1st June 2020) - Beer, Linda; Tie, Yunfeng; Smith, Dawn K.; Fagan, Jennifer L.; Shouse, R. Luke
Abstract : Objective: To estimate the proportion of US HIV-positive men who report a male HIV-negative/unknown status (HIV-discordant) sexual partner taking preexposure prophylaxis (PrEP), and the use of multiple HIV prevention strategies within partnerships. Design: The Medical Monitoring Project is a complex sample survey of US adults with diagnosed HIV. Methods: We used data collected during June 2016 to May 2018 among sexually active HIV-positive men who had at least one HIV-discordant male partner ( N  = 1871) to estimate the weighted prevalence of reporting at least one partner taking PrEP. Among HIV-discordant partnerships ( N  = 4029), we estimated PrEP use, viral suppression among HIV-positive partners, and condomless anal sex. We evaluated significant ( P  < 0.05) differences between groups using prevalence ratios with predicted marginal means. Results: Twenty-eight percent of sexually active HIV-positive MSM reported at least one HIV-discordant male partner taking PrEP. Twenty percent of HIV-discordant partners were reported to be taking PrEP; 73% were taking PrEP or the HIV-positive partner was virally suppressed. PrEP use was lower among black and Hispanic partners compared with white partners (12% and 19% vs. 27%). Fewer black than white MSM were in partnerships in which PrEP was used or the HIV-positive partner had sustained viral suppression (69% vs. 77%). Condomless anal intercourse was more prevalent in partnerships involving PrEP use and in partnerships involving either PrEP use or sustained viral suppression among the HIV-positive partner. Conclusion: PrEP use was reported among one in five partners, with disparities between black and white partners. Increasing PrEP use and decreasing racial/ethnic disparities could reduce disparities in HIV incidence and help end the US HIV epidemic.